Acute liver failure complicating viral hepatitis A - Daniel Rui Diniz-Santos (Brazilian Journal of Infectious Diseases)
Hepatitis A is one of the most frequent infectious liver diseases affecting children worldwide. The disease is usually mild and self-limited, and complications are very rare. Nevertheless, hepatitis A can sometimes cause acute liver failure (ALF), a severe, life-threatening condition. Herein is reported a case of a child who presented ALF during a course of hepatitis A. The need for early identification of possible ALF cases among hepatitis A patients, and for effective ways of evaluating such a possibility, are discussed. We also emphasize the importance of prevention measures, especially vaccination.